3m=m-2

Simple and best practice solution for 3m=m-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3m=m-2 equation:


Simplifying
3m = m + -2

Reorder the terms:
3m = -2 + m

Solving
3m = -2 + m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-1m' to each side of the equation.
3m + -1m = -2 + m + -1m

Combine like terms: 3m + -1m = 2m
2m = -2 + m + -1m

Combine like terms: m + -1m = 0
2m = -2 + 0
2m = -2

Divide each side by '2'.
m = -1

Simplifying
m = -1

See similar equations:

| 7p-2=2p+3p+12 | | (200x^2)-9000x+99072=0 | | 5-(n-4)=3(n++2) | | 8x+4x=4x-16 | | n+1-1-15=3n-1 | | p-1+6=5-3p | | 86-(21x-(17x+25))=16x-449 | | 14=2y-10 | | 3x+2=2(x+1)+3 | | 93x=400 | | -2x+4=50 | | 75x=50-25x | | 4(x+4)=2(17-2x) | | 1+4n=2n+13 | | -9(x+1)=27 | | -2x-12=-3x+12-9 | | 10(x-9)=30 | | -3x-5=6x+7 | | 7x-(8x+(5x-30))=12 | | 3b+3s=21 | | 6v+10=64 | | x^2+2x+1=65 | | 3(cx+1)=6x+4 | | 6x+5+4x=66+4x | | -4=5t+6 | | (4x^2)+4=9 | | 5(5x-2)=153+2(20-2x) | | x+8=4.24 | | -6+8r=-6+8r | | S+26=8 | | x-6=-27 | | 0.2x+7.2=10 |

Equations solver categories